GUIDEPOSTS FROM COLLEGIATE TO PRACTICING SENIOR. - Shomler, Russell P. (The Accounting Review, 1953)
The transition from an academic to professional career is a major achievement and one that can be accomplished most efficiently by a working association with those practicing in the professional field. The desirability of a period of professional apprenticeship is recognized by most states in the requirements to be fulfilled in order to receive a certificate as a public accountant and by some schools in their recent efforts toward establishing, as an integral part of the curriculum, a period of time during which each accounting major works on the staff of a certified public accountant firm. This being the case, the college senior who desires a certificate must first secure employment. Some of the principal touchstones of a desirable staff accountant to which a prospective employer will give consideration can be academic accomplishments in all courses, particularly accounting and related subjects, ratings received in the achievement, orientation, and vocational preference tests sponsored by the American Institute of Accountants, extent of participation in extracurricular activities of the school such as athletics, arts, and other group activities, personal appearance, use of the English language and sincere desire for professional success.